ADVANTAGES AND DISADVANTAGES OF ONLINE LEARNING RESOURCES IN TEACHING ENGLISH LANGUAGE SKILLS (LISTENING, READING, SPEAKING, WRITING) (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
Annotation: This thesis explores the transformative potential of online games in revolutionizing English language learning. It argues that traditional methods often fall short in engaging students, while online games provide a dynamic and immersive platform for acquiring all four language skills: listening, reading, speaking, and writing. The interactive nature of these games fosters intrinsic motivation, personalizes learning experiences, and provides instant feedback, ultimately leading to enhanced language proficiency.